Public innovation from regional government after covid-19 - Delipiter Lase; Indra Kertati; Agus Bambang Nugraha; Bambang Irawan; Wahyu Wirasati (Jurnal Komunikasi Profesional, 2023)
The COVID-19 pandemic has brought about unprecedented challenges to governments worldwide, necessitating innovative approaches to public administration and service delivery. This paper presents a case study conducted at Semarang Government, Indonesia, to explore the emergence of public innovation in the wake of the COVID-19 pandemic. The research methodology employed Content Analysis by Krippendorff to examine a wide range of textual data, including policy documents, official statements, and public communications. The study investigates how Semarang Government responded to the COVID-19 crisis by implementing innovative solutions, policies, and practices across various public sectors. The analysis aims to uncover the underlying themes, patterns, and trends in these innovative initiatives, shedding light on the strategies employed by regional governments to address the multifaceted challenges posed by the pandemic. The findings of this research not only contribute to our understanding of public innovation dynamics within regional governments but also provide valuable insights into the adaptability and resilience of public administrations in the face of global crises. Moreover, the application of Content Analysis by Krippendorff offers a robust and systematic approach for analyzing textual data, which can be replicated in similar studies to assess public innovation in different contexts.